Correction to: Metabolomic profiling identifies distinct phenotypes for ASS1 positive and negative GBM - Lina Mörén; Richard Perryman; Tim Crook; Julia K. Langer; Kevin Oneill; Nelofer Syed; Henrik Antti (BMC Cancer, 2018)
Abstract In the original publication of this article [1], published on 8 February 2018, it was noticed that the acknowledgement of the source of the drug ADI-PEG20 was missing.